(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
This article discusses a technique for measuring the surface topography by interferometry using two or more wavelengths. Unlike classical holographic interferometry, which uses photographic plates, in digital holography both holograms can be reconstructed separately using the required wavelengths.